Efficacy and safety of ivabradine in patients with chronic systolic heart failure according to blood pressure level in SHIFT. (24th June 2014) - Komajda, Michel; Böhm, Michael; Borer, Jeffrey S; Ford, Ian; Robertson, Michele; Manolis, Athanasios J.; Tavazzi, Luigi; Swedberg, Karl; on behalf of the SHIFT Investigators
<x xml:space="preserve">Abstract</x> Aims Low systolic blood pressure (SBP) is associated with poor outcomes in heart failure and complicates management. In a post hoc analysis, we investigated the efficacy and safety of ivabradine in the SHIFT population divided by tertiles of baseline SBP. Methods and Results The analysis comprised 2110 patients with SBP <115 mmHg, 1968 with 115≤ SBP <130 mmHg, and 2427 with SBP ≥130 mmHg. Patients with low SBP were younger, had lower ejection fraction, and were less likely to be at target beta‐blocker dose than patients in the other SBP groups. Ivabradine was associated with a similar relative risk reduction of the composite outcome in the three SBP groups [SBP <115 mmHg, hazard ratio (HR) = 0.84, 95% confidence interval (CI) 0.72–0.98; 115≤ SBP <130 mmHg, HR = 0.86, 95% CI 0.72 to 1.03; SBP ≥130 mmHg, HR = 0.77, 95% CI 0.66 to 0.92; P interaction = 0.68]. Similar results were found for cardiovascular mortality (P interaction = 0.91), hospitalization because of heart failure (P interaction = 0.79), all‐cause mortality (P interaction = 0.90), and heart failure mortality (P interaction = 0.18). There was no evidence for a difference in safety profile according to SBP group. Conclusion The efficacy and safety of ivabradine is independent of SBP. This may have implications for the management of HF patients with low SBP and elevated heart rate.